Genetic analysis of Drosophila neurons: Shal, Shaw, and Shab encode most embryonic potassium currents. - Tsunoda, S.; Salkoff, L. (Journal of Neuroscience, 1995)
In this study, we perform the first genetic analysis of K+ currents in Drosophila embryonic neurons revealing the identity of the currents present. Unlike muscles, where the presence of Shaker is obvious, Shaker currents are not detectable in these neurons. In contrast, we show that Shal is as important in these neuronal cell bodies as Shaker is in muscles. Only three single-channel currents were found, all of which are genetically separable. Shal encodes a 4 pS transient channel. Whole-cell Shal currents have a wide variety of inactivation rates which, in contrast to a mechanism such as heteromultimer formation, is due to single Shal channels assuming different gating modes. Shaw encodes a 42 pS noninactivating channel distinctive for its extremely low voltage sensitivity; Shaw channels have a total equivalent gating charge of 0.90 e- charges, in sharp contrast to 7 e- reported for Shaker channels. An 11 pS slowly inactivating channel also present in these neurons may be encoded by the Shab gene. Thus, of four voltage-dependent K+ channel genes now cloned in Drosophila, all except Shaker appear to be expressed in the cell bodies of these neurons. It is only in Drosophila that a study such as this one can be done. Because Drosophila contains only a single member of each of the four subfamilies of K+ channel genes (unlike mammals), we can eliminate an entire subfamily with a mutation to a single gene. Here, we have examined the effect of eliminating each of three subfamilies. Such a task is presently impossible to accomplish in any mammalian system.